3D-QSAR and molecular recognition of Klebsiella pneumoniae NDM-1 inhibitors. Issue 9 (13th June 2019) - Duan, Huaichuan; Liu, Xinyu; Zhuo, Wei; Meng, Jian; Gu, Jinke; Sun, Xin; Zuo, Ke; Luo, Qing; Luo, Yafei; Tang, Dianyong; Shi, Hubing; Cao, Shenghua; et al.
ABSTRACT: New Delhi metallo-β-lactamase-1 (NDM-1) as a target for the development of anti-superbug agents, plays an important role in the resistance of β-lactam antibiotics and has received worldwide attention. Sulfhydryl propionic acid derivatives can effectively inhibit the catalytic activity of NDM-1, but the quantitative structure–activity relationship (QSAR) and inhibitor-target recognition mechanism both remain unclear. In this work, CoMFA and CoMSIA models of sulfhydryl propionic acid inhibitors with high predictive ability were obtained, from which the effect of different substituents on the inhibitory activity against NDM-1 were revealed at the molecular level. Then, two 120-nanosecond comparative molecular dynamics (MD) simulations for NDM-1 enzyme and NDM-1-inhibitor complex systems were performed to study the recognition and inhibition mechanism of sulfhydryl propionic acid derivatives. The binding of inhibitors alters the entire H-bond network of the NDM-1 system accompanied by the formation of strong interactions with I35, W93, H120, H122, D124, H189 and H250, further weakens the recognition of NDM-1 by its endogenic substrates. Finally, the results of free energy landscape and conformation cluster analyses show that NDM-1 underwent a significant conformational change after the association with sulfhydryl propionic acid inhibitors. Our findings can provide theoretical support and help for anti-superbug agents design based on the structures of NDM-1 and sulfhydryl propionic acid derivatives.